EFFICACY OF REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION AS UPPER EXTREMITY MOTOR REHABILITATION THERAPY AFTER STROKE: A SYSTEMATIC REVIEW - Purwandhono, Azham; Adji, Novan Krisno; Abrori, Cholis; Fatmawati, Heni; Habibi, Ali (MNJ (Malang Neurology Journal), 2025)
Background: The most frequent impairment following a stroke is the hemiparesis of the opposite-side upper extremity. Repetitive Transcranial Magnetic Stimulation (rTMS) is popular in research studies on upper extremity motor rehabilitation after stroke. Information regarding the onset of therapy, duration of therapy, and the type of rTMS in post-stroke upper extremity motor rehabilitation therapy is still spread in various journals, therefore researchers are interested in making this systematic review. Objective: This study aimed to assess the efficacy of rTMS for upper extremity motor rehabilitation after stroke, and had specific aims to compare different treatment timings and durations, as well as evaluating the effectiveness of high-frequency versus low-frequency rTMS. Methods: Literature search was conducted with multiple electronic databases, such as PubMed, ScienceDirect, Cochrane Library, and LinkSpringer. The boolean operator method will be used for the keywords and the synonyms were searched using the Medical Subject Heading (MeSH) database. Critical appraisal and Risk of biases were assessed for each study using The Joanna Briggs Institute (JBI) Critical Appraisal Tools. Data analysis in this systematic review are using descriptive analysis. Results: The included studies consisted of two types of rTMS with varying onset and duration of the therapy. The duration of rTMS therapy consists of 5-18 sessions. In the Upper Extremity Fugl-Meyer Assessment (UE-FMA) based study, High-Frequency (HF) rTMS had significant overall results when compared to sham, whereas Low-Frequency (LF) rTMS therapy still showed contradictory results. HF-rTMS therapy can be performed in acute, subacute, and chronic stroke phases. The duration of HF-rTMS therapy can be done with 5 or 10 sessions, but it still needs further research in order to determine the number of sessions that have the best efficacy. Conclusion: This study show HF-rTMS has better efficacy compared to LF-rTMS for upper extremity motor rehabilitation therapy after stroke.